Seabed fluid flow in the China Seas - Zhu, Chaoqi; Li, Qingping; Li, Zhenghui; Duan, Minliang; Li, Sanzhong; Zhou, Qingjie; Geng, Minghui; Chen, Jiangxin; Jia, Yonggang (Frontiers in Marine Science, 2023)
Seabed fluid flow is a widespread and important natural phenomenon in marine environments, which involves complex multi-physics, multi-process and multi-scale processes. The developments in offshore geophysical technology have facilitated the discovery of the widespread emissions of seabed fluids. For an overview on the state-of-the-art seabed fluid flow research and for obtaining a perspective on future research in the China Seas, we reviewed the data, reports, and publications particularly that associated with cold seeps such as pockmarks, seeps, domes, mud volcanoes, and gas hydrates in the Bohai Sea, the Yellow Sea, the East China Sea, and the South China Sea. This study presents the first report for seabed fluid flow on all China Seas with the basic information required to undertake additional analytical studies of these features. Furthermore, we explore processes responsible for them and their implications. Although the seabed fluid flow is widespread, dynamic, and influential, it is still poorly examined and understood. To understand seabed fluid flow in both time and space, it is important to investigate how and why these seabed fluids form and migrate.